2014
DOI: 10.1586/17512433.2014.940896
|View full text |Cite
|
Sign up to set email alerts
|

Electronically monitored dosing histories can be used to develop a medication-taking habit and manage patient adherence

Abstract: Nonadherence to prescribed medications can lead to medical complications, disease progression, hospitalizations, overestimated dosing requirements, impaired quality of life, and death, as well as incurring substantive costs for the healthcare system from suboptimal dosing during ambulatory pharmacotherapy. Adherence can be improved by helping patients build habits of taking prescribed medications, impacting day-to-day implementation of and persistence with rationally prescribed drug dosing regimens. Accurate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…The high proportion of our participants categorised as adherent using PDC may relate to the characteristics of our patient cohort, who were older community‐dwelling adults and predominantly prevalent users of antihypertensive medication. Adherence rates vary by study design, age and duration of medication use with half of patients discontinuing pharmacotherapy within the first year . Similar to these previous studies, we found consistent associations between PDC and healthcare use.…”
Section: Discussionsupporting
confidence: 88%
“…The high proportion of our participants categorised as adherent using PDC may relate to the characteristics of our patient cohort, who were older community‐dwelling adults and predominantly prevalent users of antihypertensive medication. Adherence rates vary by study design, age and duration of medication use with half of patients discontinuing pharmacotherapy within the first year . Similar to these previous studies, we found consistent associations between PDC and healthcare use.…”
Section: Discussionsupporting
confidence: 88%
“…Through social media and leaflets distributed on a university campus in the United Kingdom, we recruited 39 participants who were willing to start taking vitamin C supplements. As taking tablets and other medications can be a habitual behaviour [33], it is possible that strategies developed early could influence future strategies. Therefore, we decided to focus on younger people who may not have well-established long-term medication routines as only 19% of young adults aged 16-24 take prescribed medication vs 90% of those aged over 75 years old [34].…”
Section: Methods Participantsmentioning
confidence: 99%
“…For example, poor medication adherence may be caused by inconsistency with one's values (eg, a dislike of taking medicines), lack of knowledge (eg, not realizing the importance of regular dosing), forgetting (common with sleep deprivation 68,69 ), and lack of habit formation. 70 Dietary sodium adherence is influenced by the quantity of food intake and access to diverse food sources. 71 2.…”
Section: Theoretical Assumptions and Propositionsmentioning
confidence: 99%